Literature Review: Demographic Parameters as One of The Determinants of The Preservation of The Kalimantan Orangutan (Pongo Pygmaeus): Literature Review: Parameter Demografi Sebagai Penentu Kelestarian Orangutan Kalimantan (Pongo Pygmaeus) - Girsang, Sahat Raja Marigo; Marpaung, Sutan Sahala Muda; Has, Dini Hardiani (Buletin Peternakan Tropis, 2024)
Orangutans are one of the priorities of 25 species whose distribution in Indonesia is only found on the Islands of Kalimantan and Sumatra. Measuring orangutan sustainability in nature generally only uses nest surveys and population density. Most studies of demographic parameters for primates are limited to long-tailed monkey requirements for harvest quotas. This research aims to identify variables measuring the demographic parameters of the Kalimantan orangutan population. The methods used in this literature review are descriptive and quantitative, taken from scientific sources (journals, theses, online media) is relevant. Findings through literature reviews show that an unbalanced general structure, reproductive disorders, fertility, inbreeding, and an unbalanced sex ratio can cause population decline. Minimum Viable Population (MVP): Bornean orangutans are estimated to be able to survive 99% in 100 years a year, namely 250-500 individuals. Research concludes that the factor that is a strength in preserving Kalimantan orangutans is their long lifespan of ± 50 years. The threat to preserving Bornean orangutans is that only one child is produced during the reproductive period. External factors that influence age distribution are environmental factors and disease.